2021
DOI: 10.1007/s10457-020-00585-4
|View full text |Cite
|
Sign up to set email alerts
|

Enteric methane mitigation and fermentation kinetics of forage species from Southern Mexico: in vitro screening

Abstract: The Alliance of Bioversity International and the International Center for Tropical Agriculture believes that open access contributes to its mission of reducing hunger and poverty, and improving human nutrition in the tropics through research aimed at increasing the eco-efficiency of agriculture.The Alliance is committed to creating and sharing knowledge and information openly and globally. We do this through collaborative research as well as through the open sharing of our data, tools, and publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 32 publications
2
17
0
3
Order By: Relevance
“…Results in CH4 reduction were also observed in the screening carried out by Valencia-Salazar et al [19] with S. mombin, P. aculeata and B. simaruba and high CH4 production with B. alicastrum.).…”
Section: Methane Productionsupporting
confidence: 64%
See 3 more Smart Citations
“…Results in CH4 reduction were also observed in the screening carried out by Valencia-Salazar et al [19] with S. mombin, P. aculeata and B. simaruba and high CH4 production with B. alicastrum.).…”
Section: Methane Productionsupporting
confidence: 64%
“…Under these conditions, most of the dry matter consumed by cattle comes from medium to low quality pastures [18] and the dry seasons contribute to a scarce supply of forage and a decrease in consumption causing the animals to only cover their maintenance requirements. In this sense, five novel tropical tree species with forage potential evaluated in this study were collected at the Lacandon rainforest, one of the most important ecosystems in Mexico, however one of the main economic activities is extensive cattle production that has generated significant deforestation in the region [19]. By using the Global Forest Watch Pro platform (https://www.globalforestwatch.org), the loss of tree cover was monitored between 2011 to 2019.…”
Section: Figure 1 Hydrogenotrophic Methanogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Blümmel et al (1997) suggested that a feed consisting of a mix of different kinds of ingredients can result in asynchrony in releasing nutrients, thus changing both the biomass of microorganisms produced and gas produced by them. In addition, one factor that can affect the fermentation and gas production of feeds is the configuration of their cell wall polysaccharides (Molina-Botero et al, 2020, Valencia-Salazar et al, 2021. Therefore, the digestibility values depend upon their composition of structural carbohydrates, including the concentration of lignin (Barahona and Sánchez, 2005) and FIGURE 1 | Modeled mean accumulated gas production (mL g −1 OM) for UHC, CB, LD, and 6 dietary mixtures.…”
Section: Discussionmentioning
confidence: 99%